Felis margarita (Carnivora: Felidae). (31st August 2015) - Cole, F. Russell; Wilson, Don E.
Abstract: Felis margarita Loche, 1858 is a felid commonly called the sand cat. It is 1 of 6 species in the genus Felis. One of the smallest of the wild cats, Felis margarita, is adapted behaviorally and morphologically to live in desert environments. Prey includes rodents, birds, reptiles, and arthropods. This species has a wide, but disjunct distribution through northern Africa, the Arabian Peninsula, and southwest and central Asia. F. margarita occurs at low densities throughout its range and is listed as "Near Threatened" by the International Union for Conservation of Nature and Natural Resources due to habitat degradation and its low and potentially declining population. F. margarita is bred in zoos in North America and Europe.